EFFECT OF Rhabdosciadium anatolyi AND CHLOROGENIC ACID ON SERUM RETINOL, CHOLECALCIFEROL AND PHYLLOQUINONE LEVELS IN EXPERIMENTAL CYCLOPHOSPHAMIDE TREATED RATS - Ahmet BAKIR; Suat EKIN; Mehmet FIRAT (Journal of Animal and Plant Sciences, 2025)
In this study, the effects of chlorogenic acid (CA), and ethanol extract of Rhabdosciadium anatolyi (R. anatolyi) flowers on the levels of vitamins (retinol, cholecalciferol and phylloquinone) in the serum of experimentally cyclophosphamide (CP)-induced rats were investigated. Wistar-albino female rats (N=48) of 8 weeks old (200-250 g) were divided into six groups of 8 animals each (control (0.9% NaCl), 200 mg/kg CP, 100 mg/kg CA, 300 mg/kg R.anatolyi flowers extract, 200 mg/kg CP + 300 mg/kg R.anatolyi flowers extract and 200 mg/kg CP + 100 mg/kg CA).At the end of the 7-day study, blood samples were collected from the rats’ heart and serum was extracted. Retinol, cholecalciferol and phylloquinone levels in the groups were determined simultaneously using simple reversed phase HPLC method. According to the results of statistical analysis, a significant difference (p<0.01, p<0.05) was observed between the control group and the groups treated with 200 mg/kg CP and 200 mg/kg CP + 300 mg/kg R. anatolyi flower ethanol extract, respectively. In addition, a significant difference (p<0.01) in cholecalciferol levels between control and 200 mg/kg CP groups was detected. However, no statistically significant difference (p>0.05) was observed between the groups in phylloquinone levels. It is concluded that CP causes free radical damage by causing oxidative stress, and retinol, is more effective and more resistant in the antioxidant defense system compared to cholecalciferol and phylloquinone.
Keywords: Rhabdosciadium anatolyi; chlorogenic acid; cyclophosphamide; retinol; cholecalciferol; phylloquinone